Twentieth century science - Henderson, Harry, 1951-; Yount, Lisa. (San Diego, CA : Lucent Books, 1997)
Provides an overview of scientific developments that have had significant impact on our world, including atomic physics, genetic engineering, and computer technology.
Includes bibliographical references (p. 104-107) and index.
Keywords: Science -- History -- Juvenile literature; Science -- History